In situ recombination for durable photoelectrocatalytic degradation of organic dye in wastewater. (January 2023) - Zhang, Xiaoyan; Liang, Xian; Xu, Mai; Wang, Jin; Wang, Fengwu; Chen, Minggong
Abstract: Photoelectrocatalysis (PEC) can effectively degrade organic pollutants by using photoelectrodes without secondary pollution. However, significant mass transport resistance and decreased catalytic activity caused by the shedding of active components remain a barrier to achieving the photocatalytic system with a high degradation rate and long-term durability. Here, an in situ recombination concept is presented to overcome this challenge. The bionic coral-like electrode, obtained by in situ assembly of UIO-66 around TiO2 nanoflowers (TNF) on Ti-foam substrate, is employed as the photoanode in PEC. Ex situ evaluation of photoelectrochemical activity demonstrates that the UIO-66@TNF/Ti-foam (U@T/T) design significantly improves the light-propagation, light-absorption and charge transfer. In Situ degradation evaluations also shows that the interesting design promotes rapid and stable degradation of organic dye (e.g. Rhodamine B (RhB)). At 2.0 V of bias potential and pH 7.0 in 5 mg L −1 RhB, under the action of active species such as ·O2 - and ·OH (proved by the degradation mechanism experiments), the removal rate of RhB can reach 96.1% at 120 min and almost complete removal at 200 min (99.1%). Graphical abstract: Image 1 Highlights: A 3D-structural design via in-situ recombination for efficient and durable mass transport in the photoelectrode. The interface modification based on host-guest interactions between active components and substrate. High-performance photoelectrode for highly efficient and sustainable degradation.